Challenges in physician supply planning: the case of Belgium - Léonard Christian; Stordeur Sabine (BMC, 2010)
Abstract Introduction Planning human resources for health (HRH) is a complex process for policy-makers and, as a result, many countries worldwide swing from surplus to shortage. In-depth case studies can help appraising the challenges encountered and the solutions implemented. This paper has two objectives: to identify the key challenges in HRH planning in Belgium and to formulate recommendations for an effective HRH planning, on the basis of the Belgian case study and lessons drawn from an international benchmarking. Case description In Belgium, a numerus clausus set up in 1997 and effective in 2004, aims to limit the total number of physicians working in the curative sector. The assumption of a positive relationship between physician densities and health care utilization was a major argument in favor of medical supply restrictions. This new regulation did not improve recurrent challenges such as specialty imbalances, with uncovered needs particularly among general practitioners, and geographical maldistribution. New difficulties also emerged. In particular, limiting national training of HRH turned out to be ineffective within the open European workforce market. The lack of integration of policies affecting HRH was noteworthy. We described in the paper what strategies were developed to address those challenges in Belgium and in neighboring countries. Discussion and evaluation Planning the medical workforce involves determining the numbers, mix, and distribution of health providers that will be required at some identified future point in time. To succeed in their task, health policy planners have to take a broader perspective on the healthcare system. Focusing on numbers is too restrictive and adopting innovative policies learned from benchmarking without integration and coordination is unfruitful. Evolving towards a strategic planning is essential to control the effects of the complex factors impacting on human resources. This evolution requires an effective monitoring of all key factors affecting supply and demand, a dynamic approach, and a system-level perspective, considering all healthcare professionals, and integrating manpower planning with workforce development. Conclusion To engage in an evidence-based action, policy-makers need a global manpower picture, from their own country and abroad, as well as reliable and comparable manpower databases allowing proper analysis and planning of the workforce.